A rua e seus olhares: A Belle Époque Carioca nas Crônicas de João do Rio e de Machado de Assis - Moura, Fabiana Silveira (2007)
This work intends to report not only the urban and literary transformations lived by the Carioca society during the period of the last two decades of the XIX century and the first two ones of the XX century, but also the social tensions in this period, trying to reconstruct the most relevant aspects of the social and intellectual history of Rio de Janeiro fin-de-siècle, through the chronicles of João do Rio and Machado de Assis.